The underestimated preventive effects of flexible sigmoidoscopy screening: re-analysis and meta-analysis of randomized trials - Brenner, Hermann; Heisser, Thomas; Cardoso, Rafael; Hoffmeister, Michael (European journal of epidemiology, 2024)
Flexible sigmoidoscopy (FS), which is less invasive, resource intensive and costly than colonoscopy, is among the recommended screening options for colorectal cancer (CRC). Four large randomized trials consistently reported statistically significant, albeit modest effects of screening by FS on CRC incidence. However, their effect estimates included cancers that were already prevalent at recruitment and could not have been prevented by screening. We performed a re-analysis and meta-analysis of two of the trials (including the largest one) to estimate reduction of truly incident cases by a single FS offered between 55 and 64 years of age among the “at risk study population” without prevalent CRC at recruitment. In meta-analyses of data reported after more than 15 years of follow-up, relative risk (95% CI) in intention-to-screen and per-protocol analyses were 0.71 (0.66-0.76) and 0.59 (0.55-0.65) for any CRC, and 0.52 (0.47-0.57) and 0.34 (0.30-0.39) for distal CRC, respectively. These results indicate much stronger effects than those suggested by the original reports and imply that a single screening FS can prevent approximately two out of three distal incident CRC cases within 15 + years of follow-up.
Online veröffentlicht: 20. Apirl 2024
Gesehen am 09.09.2024